Fan film : a produção e a interação dos fãs na internet - Falchetti, Maurício (2011)
This research aims to observe the interaction of fans who access YouTube for viewing and sharing videos such as fan films. A considerable number of fans is not satisfied in passively consume large media corporation products. They want to make something new based on the products of their admiration. This research will analyze fan films shared on YouTube, which has several tools to stimulate users’ interaction. Fan labors have been producing and sharing more since new internet technologies were developed. Fan films based on computer games and books were selected and analyzed using review and evaluation tools, available on YouTube platform. Conclusions concern basically the form and content of fans interaction on YouTube, specifically to fans fidelity regarding the original product.